Pericarditis caused by herpes zoster. Issue 3 (March 2019) - Yamanaka, Tetsuo; Fukatsu, Toru; Miyata, Koutarou; Ichinohe, Yoshimaro; Mori, Airi; Etou, Takafumi; Hirata, Yasunobu
Abstract: A 53-year-old immunocompetent male visited our hospital complaining of chest pain which persisted for 6 h. After detailed examination, the patient was diagnosed with viral pericarditis and treated with aspirin. On day 3 after admission, rash with blisters appeared on the right side of chest. Paired serum evaluation on the day of admission and 3 weeks later revealed that varicella zoster virus(VZV)titer had significantly increased, and the patient was diagnosed with pericarditis caused by herpes zoster. Although VZV is known to cause various complications, there are few reports of pericarditis associated with VZV. We should consider the possibility of concomitant pericarditis with herpes zoster. <Learning objective: Although varicella zoster virus may cause various complications, the occurrence of myopericarditis is rare. Based on this case, it is suggested that pericarditis may develop concurrently with herpes zoster. Therefore, we should consider this possibility in patients exhibiting herpes zoster on the chest.>